Acceptability and Nutritional Profile of Pigeon Pea Snack Bars for Adolescents - Sri Purnaningsih; Zidni Ilma Nafi’a; Alfan Ridha (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Adolescents commonly exhibit unhealthy snacking behaviors characterized by high-energy and low-fiber food consumption, contributing to various nutritional problems such as obesity and micronutrient deficiencies. This study aimed to evaluate the acceptability and nutritional composition of a pigeon pea (Cajanus cajan)–based snack bar developed as a high-fiber alternative snack for adolescents. A Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate) was employed. Product acceptability was assessed through a hedonic test involving 80 untrained adolescent panelists using a 5-point scale (1 = strongly dislike to 5 = strongly like). Sensory attributes evaluated included color, aroma, taste, texture, and overall acceptance. Proximate composition and dietary fiber were analyzed according to AOAC standard methods. Energy values were calculated using Atwater conversion factors. Differences between the developed product and the control snack bar were analyzed using independent sample t-tests (p < 0.05). The developed pigeon pea snack bar demonstrated significantly higher acceptance scores than the control product across all sensory attributes (p < 0.05), with a mean overall liking score of 4.7 ± 0.41. Per 30 g serving, the snack bar contained 4.2 g protein, 4.2 g fat, 15.4 g carbohydrates, and 5 g dietary fiber and provided 134.1 kcal of energy. Approximately 83% of panelists rated the product ≥4, indicating high consumer acceptance. In conclusion, pigeon pea–based snack bars are highly acceptable and nutritionally dense, suggesting strong potential as a locally sourced, high-fiber snack alternative for adolescents. Keywords: Pigeon Pea, Sensory Evaluation, Proximate Analysis, Product Development, Adolescent Nutrition.